(untitled) (Modern education and development, 2025)
This article explores the classification of vowels in linguistics, focusing on their articulatory and acoustic features. Vowels are fundamental in understanding the structure and sound systems of languages. They are classified based on several parameters, including tongue height, tongue position, lip rounding, and tenseness. This study not only provides an overview of these classifications but also reflects on their significance in phonetic studies and linguistic research. Introduction: